Effect of trays and substrates on the initial growth of mini watermelon - Gomes, R. F. [UNESP]; Diniz, G. M.M. [UNESP]; Rabelo, H. O. [UNESP]; Castoldi, R. [UNESP]; Santos, L. S. [UNESP]; Marin, M. V. [UNESP]; Braz, L. T. [UNESP] (International Society for Horticultural Science (ISHS), 2015)
The objective of this study was to evaluate the influence of tray type and substrate on the initial development of the mini watermelon hybrid 'Ki Kodama'. The following treatments were compared: Three types of tray, 128, 200 and 288 cells, and three types of substrate, Bioplant HT, Biofibra, Bioflora. Treatments were factorially combined. Evaluations were performed 30 days after sowing, and the following parameters were determined: fresh and dry weights of shoot, fresh and dry weights of root, seedling height, number of leaves, root length, stem and root diameters, and leaf and root areas. There was a significant interaction between tray and substrate treatments for fresh and dry weights of shoot and root, stem diameter, and leaf and root areas. For the factor tray, only the root diameter differed, and 128-cell trays showed better performance, while for substrate, height, root length and number of leaves showed significant differences, with Bioflora providing better development of seedlings. For the other parameters, the best performance was observed in 288-cell trays filled with Bioplant HT. The results obtained can be explained because the volume occupied by substrate in each cell varies, which causes root and leaf development also to differ. Thus, for the conditions under which the experiment was conducted, seedlings of mini watermelon 'Ki Kodama' should be grown in 128 or 288 cell trays, filled with the commercial substrate Bioplant Prata HT or Bioflora.
Keywords: Citrulus lanatus; Germination; Seedlings